Sonographic Lobe Localization of Alveolar-Interstitial Syndrome in the Critically Ill - Konstantinos Stefanidis; Stavros Dimopoulos; Chrysafoula Kolofousi; Demosthenes D. Cokkinos; Katerina Chatzimichail; Lewis A. Eisen; Mitchell Wachtel; Dimitrios Karakitsos; Serafim Nanas (Critical Care Research and Practice)
Introduction. Fast and accurate diagnosis of alveolar-interstitial syndrome is of major importance in the critically ill. We evaluated the utility of lung ultrasound (US) in detecting and localizing alveolar-interstitial syndrome in respective pulmonary lobes as compared to computed tomography scans (CT). Methods. One hundred and seven critically ill patients participated in the study. The presence of diffuse comet-tail artifacts was considered a sign of alveolar-interstitial syndrome. We designated lobar reflections along intercostal spaces and surface lines by means of sonoanatomy in an effort to accurately localize lung pathology. Each sonographic finding was thereafter grouped into the respective lobe. Results. From 107 patients, 77 were finally included in the analysis (42 males with mean age =61±17 years, APACHE II score =17.6±6.4, and lung injury score =1.0±0.7). US exhibited high sensitivity and specificity values (ranging from over 80% for the lower lung fields up to over 90% for the upper lung fields) and considerable consistency in the diagnosis and localization of alveolar-interstitial syndrome. Conclusions. US is a reliable, bedside method for accurate detection and localization of alveolar-interstitial syndrome in the critically ill.